Estudo do perfil sociocultural dos alunos da Escola de Formação de Professores (EFP) Cabinda/ Angola - ingressos no período 2010-2013 - Hamilton Pulaco Sulo (2014)
With research now presented, we analyzed the training of teachers in Cabinda, focusing on the subjects which care about teacher education. In this perspective, the research was titled: The study of sociocultural profile of students in EFP - Cabinda from 2010-2013. We seek, through research, to understand who these subjects are, their sociocultural backgrounds, what they attribute to their training, thus building a sociocultural profile. From the information gathered, we seek to understand the reasons that lead them to seek the course of teachers; describe their sociocultural reality; understand their social conditions as well as their personal and professional layout for the profession seeking. To facilitate this research, our empirical universe school are students of teacher training school (EFP) in Cabinda, where we chose a quantitative methodology, with a questionnaire that allowed the data collection that resulted in the construction of their profile. Alongside this construction, we tried to discuss the issue of teacher training in view of the Angolan context, with a historic first foray covering education reform, soon after independence and the second educational reform, resulting from the Law 13/2001 - basic law of the Angolan education system. The results showed that these students are young and poor, mostly men but with a large female representation; mostly do not have an employment contract with any institution and is popular layers with a very low socioeconomic status, and show-oriented teacher education. These students see their education, first as a hold of their dreams, as they inspire vocation for it, and, moreover, the only way to overcome the conditions of poverty they live. Consequently, the analysis of the assessment that students do about their course and teachers reveals that it is positive, so as to warrant their training.